Enhanced Bone Regeneration in Rabbit Tibial Defects Implanted with Newly Fabricated Bioceramic Bone Grafts - Demirel, Mehtap; Aksakal, Bunyamin (WILEY, 2015)
Hydroxyapatite (HA)-based biografts, HBGs, were synthesized by mixing commercial HA with some additives via solgel method. The obtained HBGs were characterized by mechanical tests, X-ray diffractometry, XRD, SEM, and FTIR. The fabricated and commercial grafts were filled into drilled zones in New Zeland rabbit tibias. The maximum stress was increased up to 332 MPa and the absorbed energy to 26.79 Joule for the yttria-added sample H50Y10. The histopathology study suggested that better bone generation was obtained in HA-based biografts than in control group, and it was shown that the currently fabricated biografts could be used for biomedical applications.
Keywords: BETA-TRICALCIUM PHOSPHATE; HYDROXYAPATITE CERAMICS; POROUS STRUCTURE; SUBSTITUTES; INTERCONNECTIONS; OSTEOCONDUCTION; NANOPOWDERS; SOLUBILITY; REPAIR; Materials Science